Thinking LGBT human rights in Guyana: A conversation with the British High Commissioner to the Co-operative Republic of Guyana, Jane Miller, OBE. Issue 2 (22nd December 2022) - Miller, Jane; Wahab, Amar
Abstract : Scholar Amar Wahab, co-editor of the Journal of Indentureship and Its Legacies, interviews British High Commissioner to Guyana, Jane Miller, OBE, about her perspectives on LGBT human rights in Guyana. They discuss issues related to the legacies of the colonial regulation of gender and sexuality, the inclusion of diverse identities, and collaboration with LGBT activist organizations in Guyana.